Development of Android Based Mathematics Learning Media for Primary School Students - Triayomi, Ria; Pamugkas, Simon Panji (Bulletin of Science Education, 2023)
This research was conducted to develop an android-based mathematics learning media design for second-grade students at Xaverius 2 Primary School Palembang. This research adopted the research procedures outlined by Borg and Gall. The findings of this research are divided into two parts. The first part of the result research pertains to the needs analysis. Based on the need analysis, it is obvious that the development of learning media design to enhance students’ independent learning at home is highly necessary. The second result research relates to the validation of the development of Android-based learning media design. The development of the android-based learning media design falls under the category of validity. Validation testing was conducted through a single assessment, The level of feasibility of Android-based Mathematics Learning Media for Elementary School Students by media experts obtained an overall average of 95.34% in the "Very Feasible" category, by material experts an overall average of 88.6% was obtained in the "Very Feasible" category, and Testing by students obtained an average of 82.47% in the "Very Appropriate" category, so it can be concluded that the Android-based learning media developed is very suitable for use. Keywords: Learning Media, Android-Based Mathematics Learning